THE CONCEPT OF "FRIENDSHIP" IN THE RUSSIAN AND UZBEK LANGUAGE PICTURES OF THE WORLD - Davlatmuratov Siroj Ravshanbekovich; Ilhomova Yorqinoy Mansurbek qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
The article examines the concept of “Friendship” in the Russian and Uzbek linguistic worldviews. The purpose of the study is to identify universal and national-cultural features of the representation of this concept in the two linguocultures. The research material includes Russian and Uzbek proverbs and sayings reflecting ideas about friendship. The study employs linguocultural, componential, and comparative methods of analysis. The results demonstrate that the concept of friendship occupies an important place in the value systems of both nations and includes such fundamental characteristics as loyalty, trust, sincerity, and mutual support. Both universal features and nationally specific characteristics of the concept have been identified. The study concludes that friendship is a significant element of the Russian and Uzbek linguistic worldviews and reflects the distinctive features of national cultural perception.